Fenologia de espécies arbóreas em floresta de planície litorânea do sudeste do Brasil - TALORA, DANIELA CUSTÓDIO [UNESP]; MORELLATO, PATRÍCIA C. [UNESP] (Sociedade Botânica de São Paulo, 2000)
O presente estudo visou determinar os padrões fenológicos reprodutivos e vegetativos para espécies arbóreas da floresta superúmida de planície litorânea e relacionar os padrões observados com os fatores próximos (abióticos) e os evolutivos (bióticos). O estudo foi realizado no Parque Estadual da Serra do Mar, Núcleo Picinguaba, Ubatuba, SP (23°22'30S; 44°46'-44°51'45W). O clima da região é tropical chuvoso, com precipitação alta e bem distribuída ao longo do ano todo. Observações fenológicas foram realizadas mensalmente, de julho de 1993 a junho de 1994 em 290 indivíduos pertencentes a 46 espécies arbóreas. A fenofase queda de folhas não foi sazonal (teste Rayleigh não significativo), enquanto as demais fenofases foram pouco sazonais (teste Rayleigh significativo, mas com valores baixos de r). A floração e o brotamento foram mais intensos nos meses mais úmidos, de novembro a fevereiro, enquanto a frutificação ocorreu ao longo do ano todo. Cerca de 90% das espécies não são decíduas, com predomínio da dispersão por animais (87%). A floresta de planície mostrou padrões fenológicos pouco sazonais, bastante distintos dos observados para as florestas semidecíduas do interior do estado de São Paulo.

The present study aimed to characterize the reproductive and leafing phenology of tree species of a coastal-plain forest from Southeastern Brazil and to relate the observed patterns with the local biotic and abiotic factors. The study was carried out in the Parque Estadual da Serra do Mar, Núcleo de Picinguaba, Ubatuba, São Paulo State (23°22'30S; 44°46'-44°51'45W). The climate is tropical-wet, with a high rainfall well distributed throughout the year. Monthly observations were carried out from July 1993 to June 1994 on 290 individuals of 46 tree species. The leaf fall was considered non-seasonal (Rayleigh test not significantly), while leaf flushing > 25%, flowering and fruiting were defined as weakly seasonal (Rayleigh test significantly, but low r values). Flowering and leaf flushing were more intense during the wettest months, from November to February. Fruit production was constant along the year. Ninety percent of the species were defined as evergreen and 87% of the species present animal-dispersed fruits. The phenological patterns observed for the coastal-plain forest at Picinguaba were weakly seasonal, contrasting with the very seasonal patterns found in the semideciduous forests from Southeastern Brazil.
Phenology of coastal-plain forest tree from Southeastern Brazil
Keywords: Phenology; Atlantic forest; flowering; fruiting